Project-Based Online Learning towards Student Creativity Development - Reny Dwi Riastuti; Ivoni Susanti; Rambat Nur Sasongko; Muhammad Kristiawan; Rahmi Rahmi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to discover student creativity during project-based online learning. The researchers illustrated how project-based online learning was implemented in Taxonomy Course and how this learning could develop the creativity of the 4.0 Industrial Revolution on student projects using a descriptive quantitative approach as the method of study. The subjects of this study were 22 UNPARI students, specifically from the Biology Education study program, with 22 female students and one male student. As a data collection technique, documentation was used in the form of student projects. A descriptive statistic was used to perform quantitative data analysis.  The data was collected using the creativity rubric and analyzed so that the results could be converted into percent (%) from each indicator. According to the findings of this study, 5 students have a very high level of creativity, 14 students have a high level of creativity, and 3 students have a moderate level of creativity.